ANALYSIS OF BANK HEALTH LEVEL USING RBBR (RISK-BASED BANK RATING) METHOD (STUDY ON PT BANK MANDIRI (PERSERO) TBK FOR THE 2018-2022 PERIOD) - Furqan Ramadhan Jazadi; Rozmita Dewi Yuniarti R (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Bank is a financial institution that makes it easier for people to save funds, need funds, their business activities are in the financial sector. Determination of bank conditions must be based on the assessment of the soundness of the bank as stated in Bank Indonesia Regulation No.13/1/PBI/2011. This study aims to determine the development of risk profile earnings, capital and health levels at Bank Mandiri for the 2018-2022 period using the RBBR (Risk-Based Bank Rating) method. This type of research is descriptive research with a quantitative approach. This study uses three of the four assessment factors, namely the risk profile using two risks, namely credit risk with the NPL ratio and liquidity risk with the LDR ratio, profitability using two ratios, namely the ROA ratio and the NIM ratio, and capital using the CAR ratio, and using the GCG factor. The results showed that Bank Mandiri's NPLs in 2018-2022 had poor developments in terms of bad loans, this was the impact of the Covid-19 pandemic. Overall, Bank Mandiri's level of soundness in 2018-2022 based on the ratio of NPL, LDR, ROA, NIM and CAR can be categorized as healthy although there are some that can also be categorized as quite healthy. Keywords: The Bank Soundness level, Risk Based Bank Rating (RBBR) method